ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN RUMAH PADA PERUMAHAN TAMAN DATARAN INDAH DI KOTA MAKASSAR - Muharram Wilham; Mukhtar Galib (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This study aims to: (1) To find out and analyze the influence of cultural, social, personal and psychological factors simultaneously (together) on the decision to purchase a house in Taman Dataran Indah Housing in Makassar City (2) To find out and analyze the influence of cultural factors , social, personal and psychological partially (individually) to the decision to purchase a house in Taman Dataran Indah Housing in Makassar City. (3) To find out and analyze which variable is the most dominant influence on the decision to purchase a house in Dataran Indah Park Housing in Makassar City. The results of this study indicate (1) The analysis shows that the independent / independent variable (X) simultaneously influences cultural, social, personal and psychological factors significantly on the decision to purchase a home in Taman Dataran Indah Housing in Makassar City by 93.7% while the remaining 6.3% is influenced by other variables not included in this study (2) The four independent / independent variables (X) have a significant partial effect on housing purchase decisions at Dataran Indah Park Housing in Makassar City with the following summary: (a ) Cultural factor variable (X1) with tcount 10,089> ttable 2,000 (b) Social factor variable (X2) with tcount 3,638> ttable 2,000 (c) Personal factor variable (X3) with tcount value 3,020> ttable 2,000 (d) Variable psychological factors (X4) with a tcount of 5.680> ttable 2,000 (3) Among cultural, social, personal and psychological factors, the cultural factor (X1) is the most dominant factor influencing the decision to purchase a house in Taman Dataran Indah Housing in Makassar City.